1989
DOI: 10.1093/ptj/69.11.923
|View full text |Cite
|
Sign up to set email alerts
|

Balance Performance and Step Width in Noninstitutionalized, Elderly, Female Fallers and Nonfallers

Abstract: The purposes of this study were to compare age, static balance performance, and step-width variables between elderly noninstitutionalized women with and without a history of falls and to determine the relationship between balance performance and step width. Each subject performed a maximum of three timed trials on the sharpened Romberg and one-legged stance tests with eyes open and with eyes closed. The first and best trial measurements were used for analysis. Each subject walked on paper walkways making ink p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(75 citation statements)
references
References 16 publications
2
71
0
2
Order By: Relevance
“…Studies with faller category 2 and faller category 1 reported variability of step width with similar ES values [5,8,53,60,72,73]; however, studies with faller category 4 [35] and faller category 1 [5,53] reported variability of step length, with ESs for step length with faller category 4 being considerably higher than that for faller category 1. None of the studies reporting gait variability incorporated a faller category 5 for their studies (figure 2).…”
Section: Fallers Versus Non-fallersmentioning
confidence: 87%
See 2 more Smart Citations
“…Studies with faller category 2 and faller category 1 reported variability of step width with similar ES values [5,8,53,60,72,73]; however, studies with faller category 4 [35] and faller category 1 [5,53] reported variability of step length, with ESs for step length with faller category 4 being considerably higher than that for faller category 1. None of the studies reporting gait variability incorporated a faller category 5 for their studies (figure 2).…”
Section: Fallers Versus Non-fallersmentioning
confidence: 87%
“…After screening, 29 articles were considered eligible for inclusion in this review (figure 1). Twenty-one studies considered research questions focussed on OY [6,8,34,35,52,59,[63][64][65][66][67][68][76][77][78][80][81][82][83][84][85], whereas only 10 studies were designed to assess FNF [5,8,35,53,60,62,[72][73][74][75]. Granata & Lockhart [35] and Khandoker et al [8] presented a combination of both cohort comparisons within the same study.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gabell and Nayak suggested that an increase in mean step width indicates a lack of compensation for disturbances causing instability [25]. Heitmann et al demonstrated a negative correlation between balance performance and step width means and variability in elderly females [26]. If step width indicates stability, then the significant decrease in step width that occurred when the AFO was worn might suggest improved stability.…”
Section: Discussionmentioning
confidence: 99%
“…In addition the variability of stride length was minimal at a certain speed and a certain cadence (Sekiya et al, 1997). In women aged over 60, variability in foot width was negatively correlated with balancing abil ity (Heitmann et al 1989). Further, in terms of energy consumption, there was a study on the optimal cadence of walking speed (Zarrugh and Radcliffe, 1978).…”
mentioning
confidence: 99%